SISTEM MONITORING KEBAKARAN HUTAN BERBASIS INTERNET OF THINGS (IoT) - Jesi Pebralia; Rustan Rustan; Rizqa Raaiqa Bintana; Iful Amri (Komunikasi Fisika Indonesia, 2022)
In this study, a forest fire monitoring system based on IoT has been developed where the parameters used include temperature, wind speed, air humidity, and hotspots. These physical parameters are measured in real time using sensors installed in locations prone to forest fires. The sensor measurement data sent and processed by the Arduino Uno microcontroller and sent to the server using the Internet of Things (IoT). The forest fire monitoring system developed has a high level of accuracy, where the temperature sensor has an accuracy of 99.9%, the air humidity sensor has an accuracy of 97.85%, and the wind speed sensor has an accuracy of 90.70%. The hotspot detection system also has good performance, where the sensor can detect the presence of hotspot in real time. The development of an IoT system for monitoring four forest fire parameters was made using the Blynk application. The system can work well where data from the four forest fire parameters can be monitored in real time via computer devices or via smartphones.